KEBIJAKAN PEMBANGUNAN PERBATASAN DAN KESEJAHTERAAN MASYARAKAT DI WILAYAH PERBATASAN PULAU SEBATIK, INDONESIA - Sonny Sudiar (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
The main issue of this article is all about the development policy and prosperity of the people in the border area. Development policy becomes the key role in order to increase the quality of social life especially for the people in Sebatik Island. This article is an effort to capture the implemented policy and the real condition in particular after the enlargement of Sebatik Island. The instruments of analysis are the concept of development and the welfare state. The research findings show that development policy in the border didn’t go with the basic human need. So it is important for the government to apply the participatory model in excuting development programs.